Ultrasound-Guided Tube Cystostomy with Ammonium Chloride Orally for the Treatment of Obstructive Urolithiasis in Male Buffalo Calves - Kumar, Amit; Saharan, Sandeep; Kumar, Naveen; Kumar Tiwari, Deepak; Sharma, Maneesh; Kumar Gahlot, Parveen (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
The present study was carried out to evaluate the efficacy of ammonium chloride for the treatment of obstructive urolithiasis in male buffalo calves. Six clinical cases of obstructive urolithiasis having intact urinary bladder formed the materials of the study. The confirmed cases of obstructive urolithiasis (diagnosed based on history, clinical signs, ultrasonography, haemato-biochemical and urine analysis) were managed by ultrasound-guided tube cystostomy along with ammonium chloride administered orally @ 500 mg/kg body weight once a day for 25 days. At various postoperative intervals, variations in haemato-biochemical and urine parameters were noted, i.e., soon after surgical procedure, after 24 h of surgery, and after complete recovery. The pre-operative altered haemato-biochemical and urine profile was found to be normalized post-operatively after complete recovery from the obstructive urolithiasis and the ammonium chloride resolved the struvite uroliths from the urine. The median time required for initiation of dribbling of urine normally through the urethra post-operatively was 10 (7-13) days, and the free flow of urine from the urethral orifice was found in 13 (10-17) days. From the present study, it may be concluded that ultrasound-guided tube cystostomy is a very effective method for the treatment of obstructive urolithiasis in male buffalo calves along with ammonium chloride as urine acidifier and solvent of struvite uroliths.